Analysis of the Internalization of Islamic Religious Education Values in the Formation of Morals at Putera Muhammadiyah Orphanage Medan - Darmawan, Ikhsan; Pasaribu, Munawir; Sofyan, Sofyan (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study aims to analyse the practice of internalising Islamic religious values in the formation of children's morals at the Putera Muhammadiyah Orphanage, Medan Kota Branch. Using a qualitative approach with a case study design, this research directly observed the process of religious education implemented at the orphanage as well as the role of caregivers and administrators in supporting the moral formation of foster children. Data collection techniques involved in-depth interviews with administrators, caregivers, and foster children, as well as participatory observation, to gain a deep understanding of the interactions within the orphanage environment. The collected data were thematically analysed with a focus on the internalisation of religious values, the factors that influence its success, and the methods used to shape morals. The results showed that the process of internalising Islamic religious values at the Putera Muhammadiyah Orphanage Medan Kota Branch has been going well. However, some challenges need to be overcome. The methods used to shape children's morals include lectures, exemplary behaviour, habituation, advice, rewards and punishments, and the story method. However, there are problems related to the inability of some children to understand and realise the expectations of leaders and administrators, low awareness of personal responsibility, and limited facilities and infrastructure available. To improve the effectiveness of internalising these values, it is suggested that children's awareness be increased through more interactive learning approaches, as well as improving the quality of caregivers and facilities that support education. This study suggests the need for continuous efforts in improving the quality of education and supervision and fulfilling adequate resources to strengthen the process of internalising morals in orphanages.